2022
DOI: 10.1371/journal.ppat.1010237
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale CRISPR screening reveals that C3aR signaling is critical for rapid capture of fungi by macrophages

Abstract: The fungal pathogen Histoplasma capsulatum (Hc) invades, replicates within, and destroys macrophages. To interrogate the molecular mechanisms underlying this interaction, we conducted a host-directed CRISPR-Cas9 screen and identified 361 genes that modify macrophage susceptibility to Hc infection, greatly expanding our understanding of host gene networks targeted by Hc. We identified pathways that have not been previously implicated in Hc interaction with macrophages, including the ragulator complex (involved … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 103 publications
(204 reference statements)
2
11
0
Order By: Relevance
“…In this manner, we identified Gβ subunits that either positively or negatively regulated phagocytosis. Consistent with prior work (38,39), HL-60 neutrophils lacking Gβ 2 exhibited a ~50% reduction in particle uptake (Fig. 1B).…”
Section: Gβ 4 Deficiency Enhances Phagocytic Responses Against a Wide...supporting
confidence: 92%
See 1 more Smart Citation
“…In this manner, we identified Gβ subunits that either positively or negatively regulated phagocytosis. Consistent with prior work (38,39), HL-60 neutrophils lacking Gβ 2 exhibited a ~50% reduction in particle uptake (Fig. 1B).…”
Section: Gβ 4 Deficiency Enhances Phagocytic Responses Against a Wide...supporting
confidence: 92%
“…Heterotrimeric G proteins regulate phagocytosis and migration in multiple myeloid cell types by transducing signals from seventransmembrane G protein-coupled receptors (GPCRs) (35)(36)(37)(38)(39)(40)(41)(42). GPCR activation induces dissociation of the G protein α subunit (Gα) from the βγ subcomplex (Gβγ), freeing both components to bind and activate specific downstream effector molecules (43).…”
Section: Gβ 4 Deficiency Enhances Phagocytic Responses Against a Wide...mentioning
confidence: 99%
“…In this manner, we were able to identify G-subunits that either positively or negatively regulated phagocytosis. Consistent with prior work (Cohen et al 2022;Kamber et al 2021), HL-60 cells lacking G-2 exhibited a 50 percent reduction in particle uptake (Fig. 1b).…”
Section: G-4 Deficiency Enhances Phagocytic Responses Against a Wide ...supporting
confidence: 91%
“…To identify novel mechanisms controlling phagocytosis and functional crosstalk, we performed a candidate screen focused on heterotrimeric G-protein signaling, which regulates phagocytosis and migration in multiple myeloid cell types(Peracino et al 1998; Wen et al 2019; Pan et al 2016; Cohen et al 2022; Kamber et al 2021; Yamada and Sixt 2019; Schwarz et al 2017; Sarris and Sixt 2015). Activating signals induce the dissociation of the G-protein α subunit (G α ) from the βγ subcomplex (G βγ ), freeing both components to bind and activate specific downstream effector molecules(Clapham and Neer 1997).…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, Sil et al. performed a host-directed CRISPR/Cas9 screen in the mouse mononuclear macrophage cell J774A.1 cell line to explore the interaction mechanism between H. capsulatum and macrophages ( 135 ). They found that the C3a receptor (C3aR) was important in macrophages capturing pathogenic fungi.…”
Section: Crispr Screening In Immune Cellsmentioning
confidence: 99%